Lessons From The Field: An Insight Into The Documentation Of Gurenɛ Oral Genres - Atintono, Samuel Awinkene (My University, 2022)
The paper discusses my eight months fieldwork experience of documenting endangered Gurenɛ (Mabia, Niger-Congo) oral genres which include riddles and folktales, sung folktales, songs and ritual performances between 2010 and 2012 in Bolga and Bongo in northern Ghana. It presents the documentary corpus of close to 100 hours of both audio and video recordings and discusses the strategies and challenges of documenting these genres. It is argued in this paper that though Gurenɛ with a speaker population of over 600,000 is not endangered, its oral genres such as riddles and folktales are vanishing and deserves attention to be documented. The paper draws attention of linguistic field workers and language documenters to pay attention to such languages and not to focus only on endangered or moribund languages. The documentation corpus from this project has been archived at the Endangered Languages Archive (ELAR) at SOAS, London. The lessons in this project can be used to document these genres in other Ghanaian or African languages for revitalization and preservation of these linguistic and cultural resources of language communities.
Keywords: Gurenɛ oral genres; documentation; African languages